The facts and fictions of religion: make believe on Avatar Forums - Coleman, Elizabeth Burns (Journal of contemporary religion, 2017)
Recent scholars of religion have begun to explore the relationship between religion and fiction. Within this context, Johan Huizinga's theory of religion as make believe or play has received considerable attention. James Cameron's film Avatar (2009) has inspired behaviour that can be thought of as religious, despite the film's clear foundations in fiction. Scholarship on fan communities has debated whether such groups can be considered religions. This article develops Huizinga's account using Kendall Walton's theory of make believe. Walton's theory enables the interpretation of fiction into overlapping games of make believe in fan communities. The conversational threads on Avatar Forums show how norms of discourse that preclude disagreement allow the frames of reality and fiction to blur. These norms of discourse provide a means of understanding the process by which media myths can become the basis of fiction-based value structures within the cultic milieu. However, the theory also presents significant problems for theorists of religion in terms of the structure of religious belief and religious experience.